2010
DOI: 10.1371/journal.pone.0009000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a High Intake of Conjugated Linoleic Acid on Lipoprotein Levels in Healthy Human Subjects

Abstract: BackgroundTrans fatty acids are produced either by industrial hydrogenation or by biohydrogenation in the rumens of cows and sheep. Industrial trans fatty acids lower high-density lipoprotein (HDL) cholesterol, raise low-density lipoprotein (LDL) cholesterol, and increase the risk of coronary heart disease. The effects of trans fatty acids from ruminants are less clear. We investigated the effect on blood lipids of cis-9, trans-11 conjugated linoleic acid (CLA), a trans fatty acid largely restricted to ruminan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 45 publications
8
86
3
Order By: Relevance
“…Noone et al (23) observed that the daily intake of 3 g CLA supplement (50:50 and 80:20) decreased LDL-C levels non-significantly in CLA groups. However, von Loeffelholz (40) claimed that CLA supplementation for 6 months increased LDL-C and Desroches et al (2005) (27) Tricon et al (2006) (55) Wanders et al (2010) (34) Sofi et al (2010) (24) Raff et al (2008) (30) Chen et al (2012) (25) Naumann et The study-specific standardized difference (Std diff) in means and 95 % CI are represented by the black square and horizontal line, respectively; the area of the black square is proportional to the specific-study weight to the overall meta-analysis. The centre of the black diamond presents the pooled standardized difference in means and its width represents the pooled 95 % CI TC concentrations significantly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Noone et al (23) observed that the daily intake of 3 g CLA supplement (50:50 and 80:20) decreased LDL-C levels non-significantly in CLA groups. However, von Loeffelholz (40) claimed that CLA supplementation for 6 months increased LDL-C and Desroches et al (2005) (27) Tricon et al (2006) (55) Wanders et al (2010) (34) Sofi et al (2010) (24) Raff et al (2008) (30) Chen et al (2012) (25) Naumann et The study-specific standardized difference (Std diff) in means and 95 % CI are represented by the black square and horizontal line, respectively; the area of the black square is proportional to the specific-study weight to the overall meta-analysis. The centre of the black diamond presents the pooled standardized difference in means and its width represents the pooled 95 % CI TC concentrations significantly.…”
Section: Discussionmentioning
confidence: 99%
“…(2010) (34) Sixty-one males and females, healthy normal weight (2012) (25) Eighty males and females, healthy overweight and obese…”
Section: Conjugated Linoleic Acid Supplementation and Tagmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In this study we describe the effect of cis-9, trans-11 CLA on BP, which was a prespecified secondary end point of the study.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were analysed for blood lipoproteins, as reported elsewhere. 10 Compliance to the diet was assessed by checking the diaries and by examining the fatty acid composition of cholesterylesters in plasma. The fatty acids in plasma cholesterylesters were analysed as described previously.…”
Section: Diet Compositionmentioning
confidence: 99%